Tinjauan Strategi Pencahayaan Alami pada Bangunan Hunian Vertikal di Iklim Tropis - Setiawan, Stefanus Alex; Elsiana, Feny (Nature : National Academic Journal of Architecture, 2025)
This paper explores the effectiveness of daylighting strategies in tropical vertical residential buildings, focusing on enhancing daylight performance to improve the physical and mental well-being of the dwellers. With more time spent indoors post-pandemic, optimizing daylight access is essential. A systematic review was conducted using databases such as Science Direct, IOP Science, and Research Gate, resulting in six studies that met the criteria of daylighting, vertical residential, and tropical context. These studies were analyzed to identify key strategies side lighting, atriums, and shading devices evaluated through metrics like Daylight Factor (DF), Spatial Daylight Autonomy (sDA), and glare indexes. Findings show that side lighting is the most common strategy, enhanced by innovations such as light shelves and adjustable shading. This approach improved Target Daylight Illuminance (TDI) by up to 300%, increased Illuminance Uniformity Ratio (IUR) by 180%, and reduced over-illumination by 32–86%. Atriums, though less frequent, showed potential in deeper layouts, increasing indoor illuminance by 0.9–19.2% and reducing corridor over lighting by 41–57.1%. Effectiveness varies by building type and climate, reinforcing the need for context-specific design. The main contribution of this paper lies in synthesizing quantitative evidence into actionable, climate-responsive design insights, providing architects with a concise reference for creating healthier and more sustainable tropical residential environments.